2021
DOI: 10.3390/biomedicines9091232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Non-Immunosuppressive MPT Pore Inhibitor Alisporivir on the Functioning of Heart Mitochondria in Dystrophin-Deficient mdx Mice

Abstract: Supporting mitochondrial function is one of the therapeutic strategies that improve the functioning of skeletal muscle in Duchenne muscular dystrophy (DMD). In this work, we studied the effect of a non-immunosuppressive inhibitor of mitochondrial permeability transition pore (MPTP) alisporivir (5 mg/kg/day), reducing the intensity of the necrotic process and inflammation in skeletal muscles on the cardiac phenotype of dystrophin-deficient mdx mice. We found that the heart mitochondria of mdx mice show an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Loss of dystrophin destabilizes the myofiber membrane to cause pathological calcium overload in the cytosol during physical activity (Bonilla et al , 1988 ; Mareedu et al , 2021 ). Cytosolic calcium overload leads to an excessive uptake of calcium by the mitochondria resulting in mitochondrial depolarization and permeability transition (Moore et al , 2020 ; Budzinska et al , 2021 ; Dubinin et al , 2021 ). While ATP depletion has been documented in mdx mice and in DMD patients (Kelly‐Worden & Thomas, 2014 ; Budzinska et al , 2021 ), the contribution of ATP hydrolysis by CV has not been tested.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of dystrophin destabilizes the myofiber membrane to cause pathological calcium overload in the cytosol during physical activity (Bonilla et al , 1988 ; Mareedu et al , 2021 ). Cytosolic calcium overload leads to an excessive uptake of calcium by the mitochondria resulting in mitochondrial depolarization and permeability transition (Moore et al , 2020 ; Budzinska et al , 2021 ; Dubinin et al , 2021 ). While ATP depletion has been documented in mdx mice and in DMD patients (Kelly‐Worden & Thomas, 2014 ; Budzinska et al , 2021 ), the contribution of ATP hydrolysis by CV has not been tested.…”
Section: Resultsmentioning
confidence: 99%
“…Similar mitochondrial fragmentation was also found in a zebrafish model for DMD. Finally, Dubinin et al [ 45 ] reported that mitochondria from mdx mice were spherical structures with an irregular organization of mitochondrial cristae, and some mitochondria contained vacuoles and abnormalities in the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the cardiac mitochondria of mdx mice also showed an increase in the level of NCLX and the rate of release of calcium ions from the organelles in exchange for Na + (Figure 2) [171]. Activation of calcium transport in the heart mitochondria of young mdx mice is also accompanied by an increase in the intensity of oxidative phosphorylation [171,175], which, as we suggest, may determine the adaptation of the heart to an increase in the level of calcium in cardiomyocytes and delay cardiac pathology. It is possible that similar reprogramming is also observed in cardiomyocytes of DMD patients showing signs of metabolic adaptation [176], but this issue needs to be studied.…”
Section: Mitochondrial Ion Channels In Dmdmentioning
confidence: 98%